«Справа Бейліса» (1911–1913 рр.): версії сучасників і причини фабрикації (до сторіччя судового процесу) - Гаухман, М.В. (Український історичний журнал, 2013)
Визначаються причини фабрикації російським урядом «справи Бейліса».
Охарактеризовано чотири версії вбивства малолітнього Андрія Ющинського:
сімейну, бандитську, ритуальну та сексуальну, з яких найбільш раціональною
та вірогідною є друга. Сформульовано причини звернення уряду до підтримки
ритуальної версії, згідно з якою М.Бейліса було обвинувачено в «ритуальному вбивстві». The article deals with the “Beilis Affair” – “ritual affair”, which ended by the court
process. In this affair Kyivan Jew, Mendel Beilis, was accused of “ritual murder” of
Christian boy Andrii Yushchyns’kyi, which had been killed in March 1911. There
was the court process in Kyiv in September – October 1913, in which M.Beilis was
acquitted by jurors. In the article is envisaged versions of A.Yushchyns’kyi’s murder,
which were formulated by contemporaries of the “Beilis Affair”: familia’s, ritual,
bandit and sexual versions. It’s asserted that the version of “bandit murder” of
A.Yushchyns’kyi is rational and believable version. Also the causes of fabrication
the “Beilis Affair” by Russian government, which supported “blood libel” of Russian
right-wing movement, are defined: 1) anti-semitism’s cause – as the general
argument toward Jewish Question; 2) party’s cause – for self-presentation as an ally
of right-wing parties; 3) anti-liberal cause – for counteracting of liberal opposition;
4) nationalist’s cause – for “otherness” Jews in the Russian national project.